A 27-year-old Female Patient with Acute nausea/vomiting and Pelvic pain; a Photo Quiz - Ozsarac, Murat; Yurumez, Yusuf; Karakayalı, Onur (Archives of Academic Emergency Medicine, 2022)
A 27-year-old female patient, G2P1, presented to the emergency department (ED) with acute onset nausea, vomiting, and mild chronic abdominopelvic pain. Physical examination revealed bilateral lower quadrant tenderness without rebound, guarding, or rigidity, and vital signs were within normal limits. Electrolytes, complete blood count, and liver and kidney function tests were normal. A pregnancy test was negative, and urinalysis did not reveal any abnormalities. No free fluid was observed in the abdominal ultrasound, and the ovaries and other intra-abdominal structures were found to be normal. The patient underwent intravenous contrast-enhanced abdomiopelvic computed tomography (CT) scan.